Microstructural and functional connectivity changes of decision-related brain networks in end-stage kidney disease patients undergoing peritoneal dialysis - Jingjing Yin; Dongxue Luo; Shuhua Ma; Chudan Cai; Xiaoyan Shi; Yanqiang Peng; Jianwei Peng; Lingyu Chen; Yanmin Zheng; Ruiwei Guo; Zelin Zhuang; Zhirong Lin; et al. (Kidney Research and Clinical Practice, 2025)
Background We aimed to explore changes in decision-related brain microstructure, brain functional activities, and functional connectivity, and their correlations with cognitive function in end-stage kidney disease (ESKD) patients undergoing peritoneal dialysis (PD). Furthermore, the impact of dialysis on these changes was examined. Methods Thirty ESKD patients undergoing PD, 20 chronic kidney disease (CKD) stage 5 patients without dialysis (predialysis CKD stage 5), and 30 healthy controls (HC) were recruited for the study. Various assessments have been conducted, including neuropsychological scale testing, decision-related behavioral tests, voxel-based morphometry, and functional magnetic resonance imaging. Results Compared to the HC group, PD patients showed decreased functional activation and gray matter volume in multiple decision-related brain areas, including the ventromedial prefrontal cortex (vmPFC), orbitofrontal cortex (OFC), and anterior cingulate cortex (ACC) (p < 0.05, false discovery rate-corrected). The default mode network (DMN) and salience network (SAN) were the primary brain regions that showed decreased functional connectivity to the vmPFC and ACC. Additionally, compared to the predialysis group, the PD group showed enhanced brain activation in decision-related brain regions such as the ACC, vmPFC, and insula. Though PD and predialysis CKD stage 5 patients performed poorly in the neuropsychological and Iowa Gambling Task (IGT), there was no significant difference between the two groups. The structure and function variabilities of the vmPFC were correlated with IGT and Montreal Cognitive Assessment score, and the activation of OFC was negatively associated with blood creatinine, cystatin, and parathyroid hormone levels. Conclusion In summary, PD can change the structure and function of decision-related brain circuits (vmPFC-OFC-ACC) and reduce integration within DMN and SAN, which is correlated with cognitive function and clinical features. Moreover, our findings may suggest the comparable capability of PD in preserving one's cognitive function and disease progression. Multimodal neuroimaging based on structure and function can provide more objective information for the early diagnosis and intervention of cognitive impairment in ESKD patients.